Education of Emotional Intelligence at School-age: An Exploratory StudyFrom the Teaching Perspective - García-Tudela, Pedro Antonio (2021)
Introduction. Currently, there is an educational trend towards an affective pedagogy. For this reason, this paper investigates the knowledge and experience that Primary Education teachers (students between 6 and 12 years old) have on emotional intelligence and their education. Methodology. One hundred teachers from Spain participate in this exploratory transactional study. Specifically, the sample obtained through a random non-probabilistic technique has answered a questionnaire from which an analysis of quantitative and qualitative data has been carried out through SPSS and Atlas.ti. Results. Concerning the theoretical knowledge about the object of study, 35 codes have been elaborated where 236 textual citations are collected; there is no positive correlation between the daily work of EI in the classroom and the different sociodemographic variables. Data also show that there are educational centers in which emotional intelligence programs are implemented for all courses; on the other hand, there is some internal incoherence in other centers. Finally, there is a significant predisposition to be trained in emotional education. Discussion and Conclusions. According to the reference authors, a remarkable part of the sample has an adequate theoretical vision of the concept of emotional intelligence. However, despite the existence of high practical involvement, it is often worked in an informal or not explicit way when the current challenge consists of developing explicit programs. New lines of research linked to the findings of this study are proposed, such as the development of a descriptive and an experimental study.